Application of Quantum Learning in Improving Science Learning Outcomes on Water Cycle Materials - Artono Arto; Ira Novianty; Ova Huzaefah; Dyah Anggun Setiasih; Sofia F Rahmani (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2025)
The purpose of this study was to overcome learning problems in grade 5 SD Islami Daarunnadwah, especially those related to learning the basic science of water recycling. The type of this research is Classroom Action Research where the research subjects are fifth-grade students of SD Islami Daarunnadwah who found 21 students. The results of the Classroom research showed an increase in learning outcomes which was shown in each cycle 1 and 2, where in cycle 1 the value of learning completeness reached a percentage of 71.43 percent and in cycle 2 it had achieved an achievement with a percentage of 100%. From the observations from observers, it also shows that the application of the quantum learning model to science learning in cycle 1 shows the number 31 which is included in the good category while in cycle 2 shows the number 37 in the good category. In this way, the application of the quantum learning model in science subjects with water cycle material has improved the learning outcomes of 5th grade students of SD Islami Daarunnadwah